Expression profiling and functional analysis of circular RNAs in vitro model of intermittent hypoxia-induced liver injury - Chen, Li-Da; Huang, Jie-Feng; Lin, Xue-Jun; Huang, Ya-Ping; Xu, Qiao-Zhen; Chen, Gong-Ping; Lin, Qi-Chang (Frontiers in Physiology, 2022)
Intermittent hypoxia (IH) is a prominent feature of obstructive sleep apnea (OSA) which is increasingly recognized as a key risk factor for liver injury. Circular RNAs (circRNAs) has been suggested to act as a regulator of multiple biological processes. However, there is no study evaluating circRNAs alterations and potential role of circRNAs in OSA-related liver injury. The present study aimed to investigate circRNA expression profiles in vitro model of IH-induced liver injury, as well as potential functional characterization of the differentially expressed circRNAs (DE circRNAs). BRL-3A cells were exposed to IH or normoxia. Cell apoptosis and cell viability were evaluated using ﬂow cytometry and cell counting kit-8, respectively. The expression profile of circRNAs was depicted by circRNA sequencing. The selected circRNAs were verified by quantitative real-time PCR (qRT-PCR). Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) analyses were employed to predict DE circRNAs functions. The circRNA-miRNA-mRNA regulatory network was constructed. IH treatment caused cell injury in BRL-3A cells. 98 circRNAs were identified as being dysregulated in IH-treated BRL-3A cells. Among them, 58 were up-regulated and 40 were down-regulated. Go and KEGG analyses suggested that the DE circRNAs were predominantly enriched in the biological process such as positive regulation of NF−kappaB transcription factor activity and pathways such as circadian entrainment, Wnt signaling pathway, MAPK signaling pathway, and protein export. 3 up-regulated circRNAs and 3 down-regulated circRNAs with high number of back-splicing sites were chosen for qRT-PCR validation and were consistent with the sequencing data. CircRNA1056 and circRNA805 were predicted to interact with microRNAs that might thereby regulate downstream genes. The study characterized a profile of dysregulated circRNAs in IH-induced BRL-3A cell injury. DE circRNAs may play vital roles in the pathophysiology of IH-induced liver injury. Our findings provide preliminary support for further research in mechanisms and a new theory for the pathogenesis of OSA-related liver injury.